PENGARUH PRESEPSI HARGA, KUALITAS PELAYANAN, ATMOSPHERE CAFE TERHADAP KEPUASAN PELANGGAN - Ulfi Setiyani; Ali Maskur (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The coffee shop business is one of the choices and the cafe shop business is a lucrative business. The purpose of this study is to describe the effect of price perception, service quality, and cafe atmosphere on customer satisfaction at Cafe Angkasa Semarang. The target market is very large, not only coffee connoisseurs, but also ordinary people. This is because coffee in a coffee shop or cafe is a timeless trend and seems to have become entrenched in Indonesian society. This business opportunity is always open and s profitable . Customer satisfaction can be used to attract consumer loyalty, and it is imperative for companies to implement good service quality so that customers or visitors can survive. The creation of customer satisfaction provides benefits, including the relationship between the company and the customer becomes familiar, the customer will buy again. This study uses primary data, which is obtained directly from the original numbers in the form of a questionnaire. The sample obtained from this study were 100 customers of Semarang space cafe. The sampling technique used in this study was random sampling. The test instrument of this research is validity test by applying KMO-MSA factor analysis. Reliability testing by applying Cronbach Alpha and hypothesis testing using multiple linear regression. The results of the study are as follows: Price perception has a significant positive effect on customer satisfaction at Cafe Angkasa Semarang, service quality has a significant positive effect on customer satisfaction at Cafe Angkasa Semarang, and the atmosphere of the cafe has a significant positive effect on customer satisfaction at Cafe Angkasa Semarang.